Exercise for Osteoarthritis: A Literature Review of Pathology and Mechanism - Kong, Hui; Wang, Xue-Qiang; Zhang, Xin-An (Frontiers in Aging Neuroscience, 2022)
Osteoarthritis (OA) has a very high incidence worldwide and has become a very common joint disease in the elderly. Currently, the treatment methods for OA include surgery, drug therapy, physical factor therapy, and exercise therapy. In recent years, the treatment of certain diseases by exercise has received increasing research and attention. Proper exercise can improve the physiological function of various organs of the body and improve the overall morphology of the body. At present, the treatment of OA is usually symptomatic. Limited methods are available for the treatment of OA according to its pathogenesis, and effective intervention has not been developed to slow down the progress of OA from the molecular level. Only by clarifying the mechanism of exercise treatment of OA and the influence of different exercise intensities on normal joints and OA patients can we choose the appropriate exercise prescription to prevent and treat OA. This review expounds on the pathology and mechanism of exercise treatment of OA and the effects of different exercise types on human OA, and found that different types of exercise, exercise intensity, and exercise time have other effects on OA. High-intensity exercise induces and aggravates OA, and moderate exercise relieves and treats OA. Aerobic exercise may be the best training method to relieve pain and improve body function. Strength training is the most effective in improving muscle strength. Neuromuscular training is the best training method to relieve OA pain. Traditional techniques such as Baduanjin, Wuqinxi, and yoga and new intervention methods such as virtual reality and sports games have been widely used in OA. We should formulate individualized exercise prescriptions according to the lesion degree and needs of OA patients.